Comparing Canada's 2018 proposed and 2022 final front-of-pack labelling regulations using generic food composition data and a nationally representative dietary intake survey - Jennifer J Lee; Christine Mulligan; Mavra Ahmed; Mary R L'Abbé (Cambridge University Press, 2024)
Abstract Objective: The objective of the study was to compare the potential dietary impact of proposed and final front-of-pack labelling (FOPL) regulations (published in Canada Gazette I (CG1) and Canada Gazette II (CG2), respectively) by examining the difference in the prevalence of foods that would require a 'High in' front-of-pack nutrition symbol and nutrient intakes from those foods consumed by Canadian adults. Design: Foods in a generic food composition database (n 3676) were categorised according to the details of FOPL regulations in CGI and CGII, and the differences in the proportion of foods were compared. Using nationally representative dietary survey data, potential intakes of nutrients from foods that would display a 'High in' nutrition symbol according to CGI and CGII were compared. Setting: Canada Participants: Canadian adults (≥ 19 years; n 13 495) Results: Compared with CGI, less foods would display a 'High in' nutrition symbol (Δ = -6 %) according to CGII (saturated fat = -4 %, sugars = -1 %, sodium = -3 %). Similarly, potential intakes of nutrients-of-concern from foods that would display a 'High in' nutrition symbol were reduced according to CGII compared with CGI (saturated fat = -21 %, sugars = -2 %, sodium = -6 %). Potential intakes from foods that would display a 'High in' nutrition symbol were also reduced for energy and nutrients-to-encourage, including protein, fibre, calcium and vitamin D. Conclusions: Changes to FOPL regulations may have blunted their potential to limit intakes of nutrients-of-concern; however, they likely averted potential unintended consequences on intakes of nutrients-to-encourage for Canadians (e.g. calcium and vitamin D). To ensure policy objectives are met, FOPL regulations must be monitored regularly and evaluated over time.